1986
DOI: 10.1021/j100281a062
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectroscopic study on polymorphism and order-disorder phase transition in oleic acid

Abstract: Infrared and Raman spectra of three crystal modifications, a, ß, and 7, of oleic acid were investigated. The spectral data of the 7 (low-melting) phase were analyzed on the basis of crystal structure determined by Abrahamsson and Ryderstedt-Nahringbauer. The reversible solid-state phase transition between y and a was followed by the infrared and Raman spectra, and it was concluded that the phase transition was of an order (7)-disorder (a) type accompanied by a conformational disordering in the methyl-sided alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
87
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(94 citation statements)
references
References 0 publications
6
87
0
1
Order By: Relevance
“…68 and 75 °C, corresponding to the melting point of the C polymorph), it indicates that only the polymorph C was present in the formulations [32]. These findings were in agreement with Kobayashi (1988), who stated that only the thermostable C-form could be formed from a melt [31]. In contrast, Corvis et al (2011) reported recrystallization of stearic acid in the Eform from a ibuprofen/stearic acid melt.…”
Section: In Vitro Drug Releasesupporting
confidence: 84%
See 1 more Smart Citation
“…68 and 75 °C, corresponding to the melting point of the C polymorph), it indicates that only the polymorph C was present in the formulations [32]. These findings were in agreement with Kobayashi (1988), who stated that only the thermostable C-form could be formed from a melt [31]. In contrast, Corvis et al (2011) reported recrystallization of stearic acid in the Eform from a ibuprofen/stearic acid melt.…”
Section: In Vitro Drug Releasesupporting
confidence: 84%
“…showed an onset melting temperature at 120.7 °C, while stearic acid and behenic acid started melting at 68.2 °C and 74.7 °C, respectively, indicating the crystalline state of these compounds. Even-numbered saturated fatty acids can crystallize in at least four polymorphs, named A, B, C and E. As form C is thermodynamically stable at high temperature, all other polymorphs irreversibly transform into form C upon heating [31]. However, as no solid-solid transformations were detected prior to the melting endotherms of stearic and behenic acid (i.e.…”
Section: In Vitro Drug Releasementioning
confidence: 99%
“…Some representative peaks were assigned to the vibrations associated with the alkyl chains and the ethylene group. [20][21][22] The most prominent vibrations are the methylene rock at 888 cm -1 , the ν(C-C) modes at 924, 1064, 1095 and 1121 cm -1 , the methylene twist at 1294 cm -1 , the methylene scissor at 1437 cm -1 and ν(C=C) at 1655 cm -1 . Raman bands associated with the carboxylate group, νs(COO -) at ∼1405 cm -1 and νas(COO -) at 1597 cm -1 , are much weaker than those of the alkyl chains.…”
Section: Raman Spectramentioning
confidence: 99%
“…Table 1 gives the assignment of the TIR-SERS spectrum along with the Raman shifts of toluene (liquid) and sodium oleate (solid). The assignment was based on previous Raman data of oleic acid, its salt [20][21][22] and toluene. Although no SERS data on oleate ion has been reported, the SERS spectra on carboxylic acids 23 and olefines 24 could be used for the assignment.…”
Section: Raman Spectramentioning
confidence: 99%
“…Even-numbered saturated fatty acids can crystallize in at least four polymorphs, named A, B, C and E. As form C is thermodynamically stable at high temperature, all other polymorphs irreversibly transform into form C upon heating [31]. However, as no solid-solid transformations were detected prior to the melting endotherms of stearic and behenic acid (i.e.…”
Section: In Vitro Drug Releasementioning
confidence: 99%